Advancing alternatives: Promoting mediation and conciliation in investor-state dispute settlement - Brian Chang; Daniel Kang (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
This Perspective considers the lessons that can be drawn from existing ISDS provisions for conciliation and mediation, and suggests improvements that can be made to future ISDS provisions. It also recommends that institutions produce guidance or templates to facilitate mediation or conciliation during ongoing arbitrations.
Keywords: 330